Towards an African-American Genealogy of Market and Religion in Rap Music. Issue 3 (27th May 2019) - Pyon, Kevin
Abstract: This essay provides a new reading of the intersections between religion and rap music in its genealogical consideration of how black laborers' orientations to the market—from the antebellum slave market to the contemporary music industry—have informed their consequent commodifications of race and religion. The essay (1) traces the informal economy and sacred world of the slaves to the twinned births of the modern black prosperity gospel and hip-hop culture and (2) connects the religio-economic modalities of postbellum peddling and celebrity preachers to contemporary black prosperity preachers and hip-hop moguls. Finally, this essay concludes that the commodified formulations of race and religion in rap music represent transformations of spiritual and market categories of "authenticity" and "freedom" which have structured and sometimes limited our understandings of distinct articulations of race, religion, and the market throughout African-American history.